STUDENTS’ ERRORS IN THE USE OF SIMPLE PRESENT TENSE IN WRITING DESCRIPTIVE TEXT AT THE ELEVENTH GRADE OF SMA NEGERI 1 TELUKDALAM - Lase, Fanismawati (Research on English Language Education, 2025)
This study investigated the students’ errors in writing descriptive text especially in the use of simple present tense made by the eleventh grade of SMA Negeri 1 Telukdalam. The objectives of the study were; (1)To describe the students’ errors, and (2)To find out the causes of the students errors. The method used in this study was qualitative method. Total of participants in this study were 34 participants. The result of the data analysis showed that; (1) Students’ errors in writing descriptive text consisted of omission, addition, misformation, and misordering. The students made errors in constructing simple present tense such as errors in constructing verbal and nominal sentences, errors in using to be, errors in applying the suffix s/es and the errors in using pronoun, (2) The causes of the students errors were interlingual and intralingual errors. In conclusion, most of students at the eleventh grade of SMA N. 1 Teluk Dalam made errors in the use of simple present tense of writing descriptive text with the highest error happened in misformation, moderate in addition, next omission and the lowest error happened in misordering. It is suggested to English teachers to improving the method of teaching the simple present tense and how to applying it in writing a text. For the students, it is suggested to learn more about the simple present tense and practice more how to using the simple present tense in conctrusting a text. And, for the next researcher can takes the useful information from this research.